2020
DOI: 10.5713/ajas.19.0608
|View full text |Cite
|
Sign up to set email alerts
|

Dietary chia (Salvia hispanica L.) improves the nutritional quality of broiler meat

Abstract: Objective: The current study was conducted to evaluate the quality and profile of fatty acid in the breast and thigh, and the performance of broilers fed diets containing seed or oil of chia (<i>Salvia hispanica L.</i>) as a replacement for soybean, in the rearing period from 29 to 42 days of age.Methods: On the 29th day of age, 120 broilers were distributed in four treatments evaluated in five replicates of six birds. The grain or oil of soybean was respectively replaced on a weightto-weight basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In our findings, an increased level of UFAs and a reduced level of SFAs as well as an improved ratio of PUFAs to SFAs in the meat of broilers supplemented with LMOA were observed, which was parallel with Galli et al [ 8 ], who indicated that dietary microencapsulated organic acids lowered the level of SFAs and increased the level of UFAs in broiler meat. This phenomenon probably resulted from the involvement of some components of MOA in fatty acid metabolism in the liver, reducing the process of ab initio synthesis of fatty acids, as well as the increased synthesis of desaturases Δ5, Δ6 [ 42 ] and Δ9 [ 27 ]. However, PUFA-enriched chicken contains a greater proportion of fatty acids with double bonds, which may influence oxidative stability and increase its susceptibility to oxidation, thus affecting the meat quality of the chicken [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our findings, an increased level of UFAs and a reduced level of SFAs as well as an improved ratio of PUFAs to SFAs in the meat of broilers supplemented with LMOA were observed, which was parallel with Galli et al [ 8 ], who indicated that dietary microencapsulated organic acids lowered the level of SFAs and increased the level of UFAs in broiler meat. This phenomenon probably resulted from the involvement of some components of MOA in fatty acid metabolism in the liver, reducing the process of ab initio synthesis of fatty acids, as well as the increased synthesis of desaturases Δ5, Δ6 [ 42 ] and Δ9 [ 27 ]. However, PUFA-enriched chicken contains a greater proportion of fatty acids with double bonds, which may influence oxidative stability and increase its susceptibility to oxidation, thus affecting the meat quality of the chicken [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This improvement may be due to several factors, such as; a) presence of a sufficient quantity of polyphenolic compounds in chia (caffeic acid, chlorogenic acid, kaemperol, myricetin and quercetin) which are potent antioxidants that can reduce the production of free radicals in the body, inhibit peroxidation of fats and have much stronger antioxidant activities than vitamin C, vitamin E and ferulic acid, b) presence of large amounts of vitamins (A, C and E) and minerals (sodium, potassium and chloride) in chia oil that might play a role in stress reduction, c) increased digestive secretion (bile and mucus) and stimulation of enzymatic activities, d) improved digestive tract motility, food taste, and immunity and antimicrobial status, e) increased trypsin, amylase and jejunal chyme secretion, f) diminished bacterial adherence (i.e. Escherichia coli and Clostridium perfringens) to the intestinal wall (Pandey and Rizvi 2009;Nadeem et al 2014;Alagawany et al 2018Alagawany et al , 2019Kulczy-ski et al 2019;Mendonc¸a et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with that of Evans (2009), and the observed level was similar to Mnisi et al (2017), who reported a normal creatinine level of 0.35 mg/dL for quail blood. These observations could be returned to absence of the toxic substances in chia seeds or oils which are present in other plant seeds or fish meals (Ting et al 1990;Ayerza and Coates 1999;Mendonc¸a et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations